2017
DOI: 10.2527/jas.2016.1081
|View full text |Cite
|
Sign up to set email alerts
|

Twin- or single-screw extrusion of raw soybeans and preconditioned soybean meal and corn as individual ingredients or as corn-soybean product blends in diets for weanling swine1

Abstract: Two 28-d experiments were conducted to evaluate the effects of extrusion of ground yellow corn, solvent-extracted soybean meal (SBM), and cracked whole soybeans (CWS) individually or as corn-soybean product blends on growth performance of weanling pigs. For Exp. 1, ground corn, SBM, and the corn-SBM blend were extruded at 137.5°C, 131.5°C, and 135.0°C, respectively, in a twin-screw extruder. Transit time was 60 s. Water was injected at 125 gmin during extrusion. The 5 treatments were the corn-SBM control diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…In the present work, corn grinding and extrusion resulted in a similar performance, consistent with other studies that also did not find the extrusion process to result in better pig growth performance than grinding (Oliveira et al, 2011;Liu et al, 2014;Veum et al, 2017). Extrusion is generally believed to provide superior performance due to its improvement in nutrient digestibility (Medel et al, 1999;Rojas et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…In the present work, corn grinding and extrusion resulted in a similar performance, consistent with other studies that also did not find the extrusion process to result in better pig growth performance than grinding (Oliveira et al, 2011;Liu et al, 2014;Veum et al, 2017). Extrusion is generally believed to provide superior performance due to its improvement in nutrient digestibility (Medel et al, 1999;Rojas et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…In our experiment the urease activity in the raw seeds exceeded 4 mgN•g −1 •min −1 , but in extruded seeds it ranged from 0.08 to less than 0.05 mgN•g −1 •min −1 , depending on the variety. Veum et al [36] confirmed the fact that after proper thermobaric treatment of soybeans the content of anti-nutritional ingredients, especially trypsin inhibitors, was significantly reduced. The treatment improved the digestibility of this soy product and resulted in high protein digestibility and energy.…”
Section: Discussionmentioning
confidence: 87%
“…There was also an increase in starch digestibility of ileum if corn, wheat, and sorghum diets were PU [ 51 ]. This increase is likely the result of starch gelatinization, which breaks down the intermolecular bonds in the starch granules so that the gelatinized starch is more readily available to intestinal enzymes [ 52 ]. The puffing increases RDS content in barley diets, peas diets, or diets containing potato starch and wheat bran, reducing RS content and thus increasing ileum starch digestibility in pigs [ 53 ].…”
Section: Discussionmentioning
confidence: 99%